Natural lipid profile mimicking diets to enhance survival and fitness of restocked salmon parr in river ecosystems? - Valérie Cornet; Anna Wanderscheid; Camille Carpentier; Alexandre Erraud; Yvan Larondelle; Christel Lefrançois; Patrick Kestemont (Aquaculture, 2026)

The Overlooked Threat of Global Warming on Elasmobranch Fertility - Noémie Coulon; Eric Feunteun; Alexandre Carpentier; Anne Lizé (Fish and Fisheries, 2026)
Climate change is increasingly recognised as a critical threat to global biodiversity, yet its impacts on reproductive processes remain poorly understood in many marine taxa. Elasmobranchs (sharks, skates and rays) represent a particularly vulnerable group due to their peculiar life histories, low fecundity, and diverse reproductive modes. In this review, we synthesise current knowledge on how rising ocean temperatures may affect elasmobranch fertility across key stages of the reproductive cycle, including gametogenesis, mate searching, sperm storage, fertilisation, embryonic development, and offspring production. Evidence from 88 species suggests that thermal stress could impair sperm and oocyte quality, disrupt reproductive timing, alter embryonic growth and survival, and potentially exacerbate sexual conflict. While some reproductive strategies such as embryonic diapause, sperm storage, or behavioural thermoregulation may provide short‐term buffering capacity, their effectiveness under rapid and sustained warming remains uncertain. We further highlight the macroevolutionary significance of elasmobranch reproductive diversity, as well as the conservation implications of fertility constraints under global change. Addressing these knowledge gaps is essential to refining demographic models, improving extinction risk assessments, and guiding the design of climate‐resilient management strategies, including fisheries regulations and marine protected areas. By explicitly linking reproductive biology with conservation policy, we argue that understanding thermal fertility limits is key to predicting elasmobranch population trajectories in a warming ocean.

Homogeneous fish communities use intertidal salt marshes at high tide, despite environmental diversity: insights from a large-scale monitoring program on French coasts - Loïc Baumann; Anthony Sturbois; Alexandre Carpentier; Aurélien Besnard; Nils Teichert; Sylvain Duhamel; Paméla Lagrange; Emmanuel Caillot (Marine Environmental Research, 2025)

Importance of the microphytobenthos in the foodweb of tropical mudflats - Alexandre Carpentier; Anne Lizé; Hien Nguyen Thanh; Pierrick Bocher; Christel Lefrançois; Antoine Gardel; Pierre-Yves Pascal; Christine Dupuy (Estuarine, Coastal and Shelf Science, 2025)

Elasmobranch vulnerability to global warming: insights from bioenergetic modelling of catsharks under climate scenarios - Noémie Coulon; Sophie Elliott; Thomas Barreau; Julie Lucas; Emma Gousset; Eric Feunteun; Alexandre Carpentier (Ecological Modelling, 2025)

Estuarine lateral ecotones shape taxonomic and functional structure of fish assemblages. The case of the Seine Estuary, France - Matia Pavkovic; Alexandre Carpentier; Sylvain Duhamel; Laure Carassou; Jérémy Lobry; Eric Feunteun; Nils Teichert (Estuarine, Coastal and Shelf Science, 2025)

Shark critical life stage vulnerability to monthly temperature variations under climate change - Noémie Coulon; Stanislas Pilet; Anne Lizé; Thomas Lacoue-Labarthe; Anthony Sturbois; Aurèle Toussaint; Eric Feunteun; Alexandre Carpentier (Marine Environmental Research, 2024)

Corrigendum to “Quantifying larval dispersal portfolio in seabass nurseries using otolith chemical signatures” [Mar. Environ. Res. 196 (2024) 106426] - Nils Teichert; Hélène Tabouret; Anne Lizé; Françoise Daverat; Anthony Acou; Thomas Trancart; Laure-Sarah Virag; Christophe Pécheyran; Eric Feunteun; Alexandre Carpentier (Marine Environmental Research, 2024)

Quantifying larval dispersal portfolio in seabass nurseries using otolith chemical signatures - Nils Teichert; Hélène Tabouret; Anne Lizé; Françoise Daverat; Anthony Acou; Thomas Trancart; Laure-Sarah Virag; Christophe Pécheyran; Eric Feunteun; Alexandre Carpentier (Marine Environmental Research, 2024)

Hydro-morphological features and functional structure of fish assemblages mediate species isotopic niches in estuaries - Nils Teichert; Anne Lizé; Mario Lepage; Henrique Cabral; Thomas Trancart; Anthony Acou; Marie Larregieu; Eric Feunteun; Alexandre Carpentier (Estuarine, Coastal and Shelf Science, 2024)

Northeast Atlantic elasmobranch community on the move: Functional reorganization in response to climate change - Noémie Coulon; Sophie Elliott; Nils Teichert; Arnaud Auber; Matthew McLean; Thomas Barreau; Eric Feunteun; Alexandre Carpentier (Global Change Biology, 2024)
While spatial distribution shifts have been documented in many marine fishes under global change, the responses of elasmobranchs have rarely been studied, which may have led to an underestimation of their potential additional threats. Given their irreplaceable role in ecosystems and their high extinction risk, we used a 24‐year time series (1997–2020) of scientific bottom trawl surveys to examine the effects of climate change on the spatial distribution of nine elasmobranch species within Northeast Atlantic waters. Using a hierarchical modeling of species communities, belonging to the joint species distribution models, we found that suitable habitats for four species increased on average by a factor of 1.6 and, for six species, shifted north‐eastwards and/or to deeper waters over the past two decades. By integrating species traits, we showed changes in habitat suitability led to changes in the elasmobranchs trait composition. Moreover, communities shifted to deeper waters and their mean trophic level decreased. We also note an increase in the mean community size at maturity concurrent with a decrease in fecundity. Because skates and sharks are functionally unique and dangerously vulnerable to both climate change and fishing, we advocate for urgent considerations of species traits in management measures. Their use would make it better to identify species whose loss could have irreversible impacts in face of the myriad of anthropogenic threats.

Biogeographical snapshot of life-history traits of European silver eels: insights from otolith microchemistry - Nils Teichert; Bastien Bourillon; Kyoko Suzuki; Anthony Acou; Alexandre Carpentier; Mari Kuroki; David Righton; Thomas Trancart; Laure-Sarah Virag; Alan Walker; Tsuguo Otake; Eric Feunteun (Aquatic Sciences, 2023)

Decoupling carry-over effects from environment in fish nursery grounds - Nils Teichert; Anne Lizé; Henrique Cabral; Anthony Acou; Thomas Trancart; Laure-Sarah Virag; Eric Feunteun; Alexandre Carpentier (Science of The Total Environment, 2023)

A multi-approach study to reveal eel life-history traits in an obstructed catchment before dam removal - Nils Teichert; Anne Lizé; Hélène Tabouret; Claudia Gérard; Gilles Bareille; Anthony Acou; Alexandre Carpentier; Thomas Trancart; Laure-Sarah Virag; Emma Robin; Morgan Druet; Jordan Prod’Homme; et al. (Hydrobiologia, 2022)

Site Characteristics More Than Vegetation Type Influence Food Web Structure of Intertidal Salt Marshes - Denis Lafage; Alexandre Carpentier; Sylvain Duhamel; Christine Dupuy; Eric Feunteun; Sandric Lesourd; Julien Pétillon (Frontiers in Marine Science, 2021)
Salt marshes are under increasing anthropogenic pressures that have been reported to affect the diet of fish (e.g., change in prey composition and availability), eventually resulting in alterations in their nursery function. Most studies in Europe are based on fish gut content analysis, which only reflect a small proportion of pressures to salt marshes, and do not necessarily reflect long-term disturbances. In this study, we investigated the impact of salt-marsh vegetation type on trophic network structures (i.e., fish diet and trophic position). Primary producers (particulate organic matter, microphytobenthos, and dominant terrestrial plants), potential aquatic and terrestrial prey, and fish of two dominant species (sea bass and thinlip mullet) were sampled during the summer of 2010 in four creeks from two sites from Western France (the Mont-Saint-Michel Bay and the Seine Estuary). Analysis was undertaken using C and N stable-isotope compositions. Tested response variables (diet and trophic position) suggested a dominant site effect and a weaker effect of surrounding vegetation type. Site effect was attributed to differences in anthropogenic nitrogen inputs (with a steep increase in the Mont-Saint-Michel Bay) and tidal regime between the two bays, with more marine signatures associated with a higher frequency and duration of tidal flooding events in the Seine Estuary. A second hypothesis is that invasive Elytrigia acuta , which has recently replaced typical salt-marsh vegetation in Mont-Saint-Michel Bay, negatively impacted the native salt-marshes nursery function by modifying the access to terrestrial prey on this site. The trophic position of the sea bass and the thinlip mullet was unchanged by local salt-marsh vegetation, and considered consistent with their diet. This study highlights the relevance of stable-isotopes analyses for assessing long-term and integrative effects of changes in vegetation resulting from human disturbances in salt marshes.

Safety of radiosurgery concurrent with systemic therapy (chemotherapy, targeted therapy, and/or immunotherapy) in brain metastases: a systematic review - Pierre-Yves Borius; Jean Régis; Alexandre Carpentier; Michel Kalamarides; Charles Ambroise Valery; Igor Latorzeff (Cancer and Metastasis Reviews, 2021)

Impact of salt-marsh management on fish nursery function in the bay of Aiguillon (French Atlantic coast), with a focus on European sea bass diet - Emmanuel Joyeux; Alexandre Carpentier; Frédéric Corre; Sylvain Haie; Julien Pétillon (Journal of Coastal Conservation, 2017)

Reproductive parameters in relation to food supply in the whiskered tern (Chlidonias hybrida) - Jean-Marc Paillisson; Sébastien Reeber; Alexandre Carpentier; Loïc Marion (Journal of Ornithology, 2007)

Plant-water regime management in a wetland: consequences for a floating vegetation-nesting bird, whiskered tern Chlidonias hybridus - Jean-Marc Paillisson; Sebastien Reeber; Alexandre Carpentier; Loic Marion (Biodiversity and Conservation, 2006)